STRATEGI KUA KECAMATAN BANYUANYAR DALAM PENCEGAHAN PERNIKAHAN DINI - Rimawati; Billah, Ana (LPPM STAI Muhammadiyah Probolinggo, 2024)
The purpose of this study is to analyze the strategic steps of the Banyuanyar District KUA to the community so that early marriage can be prevented by providing prevention efforts either through meetings with the community, especially women who have teenage children, or meetings or socialization to schools so that students understand early marriage. This study is a field study and uses a qualitative approach, and is analyzed descriptively. Data collection obtained directly based on the results of observations and interviews with sources at the location of a case or event being studied which was carried out directly by the researcher. The location of this research was carried out at the Banyuanyar District KUA office, Probolinggo Regency. The results of the study at the Banyuanyar District KUA are strategic steps in an effort to minimize or prevent early marriage which is carried out by providing a letter of rejection of early marriage. The Banyuanyar District KUA provides advice to prospective brides and grooms who are still underage so that there is no increase in early marriage. In implementing it, the KUA of Banyuanyar District provides direct socialization to teenagers in the form of character and mental development and training in order to reduce the high number of early marriages and additional funds are needed from the local government so that there is socialization of early marriage prevention either through the media or meetings in each region or area so that it can reduce or even suppress the number of early marriages. Keywords: Efforts; Prevention; Early Marriage.